Respuesta :

Answer:

Step-by-step explanation:

Pythagorean theorem: base ² +altitude² = hypotenuse²

1) hypotenuse² = base² + altitude²

          x² = 6² + 3²

               = 36 + 9

               = 45

         x = √45

         x = 6.7 cm

4) base ² +altitude² = hypotenuse²

x ² + 3.7 ² =  4.2 ²

x ² + 13.69 = 17.64

             x ² = 17.64 - 13.69 = 3.95

             x = √3.95

            x = 1.99 cm

10)c ² = a ² + b ²

           = 3 ² +4 ²

         = 9 + 16

  c ² = 25

c = √25 = 5

11) a ² + b ² = c ²

9 ² +b² = 13 ²

81 + b² = 169

     b² = 169 - 81 = 88

b = 9.38

12) a² + b² = c²

12² + b² = 22²

  144 + b² = 484

           b² = 484 - 144 = 340

           b =√340 = 18.44